Testing Hydrate Drilling Fluid Properties - Lal, B. (Springer Nature, 2022)
Drilling fluid properties are mostly measured and tuned to suit a specific function needed for drilling a particular drilling section and location. Therefore, routine measurements are conducted to ensure that the drilling mud properties are suitable at every drilling section. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.